Gene sequence diversity of the nonribosomal peptide and polyketide natural products in Changbaishan soil correlates with changes in landscape belts. (December 2021) - Zhang, Haipeng; Liu, Yuehua; Wang, Xinhai; Hu, Renge; Xu, Guanyi; Mao, Changsi; Inam, Muhammad; Wang, Yiming; Jiang, Xiuyun; Kong, Lingcong; Ma, Hongxia
Highlights: Natural products were highest richness in AT and BF belts in Changbaishan. Natural products mainly exist in unidentified bacteria, Proteobacteria and Actinobacteria in Changbaishan soil. Natural products richness was negatively correlated with the P, N, Ca, K, and OM in AT and BF belts. Abstract: Nonribosomal peptides (NRPs) and polyketides (PKs) have widely been widely applied in clinical drugs in use today, and one of the main sources for novel NRPs and PKs is soil microbes. However, the diversity of soil bacteria and distribution of their NRPs and PKs biosynthetic genes in different landscapes in extreme environments have not been reported. In this study, 16S rRNA gene fragments from five landscape belts in Changbaishan were analyzed. The results demonstrated that Acidobacteria, Proteobacteria and Chloroflexi accounted for 65% of all bacterial species. Furthermore, the diversities of the PKs and NRPs in the different landscape belts of Changbaishan were compared based on the diversity of gene fragments of the polyketide synthase (PKs) ketosynthase (KS) domain and nonribosomal peptide synthetase (NRPs) adenylation domain (AD). The results showed that NRPs and PKs had highest richness in alpine tundra and birch forest belts, which were negatively correlated with the contents of the available phosphorus, nitrogen, calcium, potassium, and soil organic matter. NRPs and PKs mainly existed in unidentified bacteria, Proteobacteria and Actinobacteria . In addition, a 16S rRNA KEGG pathway analysis showed that the soil microorganisms of Changbaishan have the potential to promote secondary metabolite biosynthesis, resist diseases and regulate immune systems. These combined results suggest that soils of alpine tundra and birch forest belts in Changbaishan may be the main sources for searching the novel antibacterial drugs.